Selected problems in the tonal manifestation of words containing assimilated or elided schwa - Thorsen, Nina (Annual Report of the Institute of Phonetics University of Copenhagen, 1982)
69 words recorded in carrier sentences by four speakers are the basis for an acoustic analysis of fundamental frequency patterns under various kinds of schwa assimilation, instigated by a previous observation of "delayed" Fo peaks in words with assimilated schwa. It turns out that the tonal reduction or assimilation - if and when it occurs - is a function of the durational reduction involved in assimilation of schwa rather than a characteristic of schwa syllables and assimilation as such. The durational modifications involved in schwa assimilation are established.